Implicit and Explicit Messages on Neighborhood Watch Signs in San Diego County, California, 2005-2007 - Schultz, P. Wesley ([Verlag nicht ermittelbar], 2010)
The purpose of the study was to evaluate the effects of Neighborhood Watch signs on perceived crime rates, likelihood of victimization, community safety, and estimates of home and community quality. Part 1 (Study One Data) assessed the causal impact of Neighborhood Watch sign presence and content on perceptions of the community. Three Neighborhood Watch signs were incorporated into a series of slide show presentations. The signs utilized the traditional orange and white color scheme with black text and were used to represent an injunctive norm alone, a low descriptive norm for crime, or a high descriptive norm for crime. Digital color images of a for-sale home and the surrounding neighborhood of a middle class community in North San Diego County were shown to 180 undergraduates recruited from the Psychology Department's Human Participant Pool, and from other lower division general education courses at California State University, San Marcos, between July and November of 2005. Three of the slide shows were designated as Neighborhood Watch communities with one of the three sign types posted, and the fourth slide show served as a control with no posted crime prevention signs. Each slide show consisted of 20 images of the home and community, along with four instruction slides. Part 2 (Study Two Data) replicated the basic effect from Study 1 and extended the research to examine the moderating role of community social economic status (SES) on the effects of the Neighborhood Watch signs. Participants were 547 undergraduate students recruited from the Psychology Department's Human Participant Pool, and from other lower division general education courses at California State University and Palomar Community College in San Marcos, between January and September 2006. A total of 12 slide shows were utilized in Study Two, such that each of the four sign conditions from Study One was represented across each of the three communities (Low, Middle, and High SES). Part 3 (Study Three Data) examined the potential for the physical condition of the Neighborhood Watch signs posted in the community to convey normative information about the presence and acceptance of crime in the community. Participants were 364 undergraduate students recruited from the Psychology Department's Human Participant Pool, and from other lower division general education courses at California State University and Palomar Community College in San Marcos, between October 2006 and March 2007. Study Three used the same generic (Injunctive Norm, Program Only) sign that was utilized in Studies One and Two. However, three variations (new, aged, and defaced) of the sign were used. The surveys used for Study One, Study Two, and Study Three, were identical. The data include variables on perceived crime rates, perceived likelihood of victimization, perceived community safety, community ratings, self-protective behavior, burglar's perspective, manipulation check, and demographics of the respondent.